Improving Students Speaking Ability Through Story Telling - Dewi Sri Merdekawati; Ernawati Humaira (Jurnal Dirosah Islamiyah, 2022)
Learning in class tenth TKJ 1 about speaking is very low, students look embarrassed and are not confident in speaking English, this is due to the lack of opportunities for students to speak. With the total 32 of students and carried out starting on july 17 to 1 august through the method of classroom action that researchers do 2 cycle of the cycle 1 and cycle 2. The researcher use story telling method for train students speaking, PTK (Penelitian Tindakan Kelas) or Action Research is research practice for improve learning in the class. Iam is the researcher do PTK (Penelitian Tindakan Kelas). Score KKM (Criteria Completeness Minimum) in SMK BNI 76 and 75% total from the students, then the results of the test are pre-test tell stories directly without preparation in front of the the classroom only 8 students that reaches KKM, 25% from 32 students with average 66. Cycle 1 tell stories about holiday there are 19 students that reaches KKM, 59,3% with average 72,75, on cycle 1 not yet reaches KKM so the next on cycle 2. Cycle 2 tell stories about experiences the result 24 students that reaches KKM, 75% from 32 students with the mean 80,25. Keyword: Speaking Ability, Story Telling, Activity